Kinetic study of the drying of the bark of jabuticaba (Myrciaria Cauliflora Berg) using empirical and semi-empirical models (Research, Society and Development, 2021)
The Jabuticabeira (Myrciaria cauliflora) is a Brazilian native fruit tree, belonging to the family Myrtaceae, its fruits have great nutritional value. Jabuticaba shells are a source of anthocyanins, which are powerful antioxidant compounds and have antimicrobial activity. However, jabuticaba peels are generally discarded, which in addition to generating polluting waste, promotes the waste of nutrients and potentially bioactive compounds present in that portion. Thus, in order to minimize the changes and losses of certain bioactive compounds, and consequently indicate the potential for using the waste on an industrial scale, the present work aims to evaluate the drying kinetics of jabuticaba bark and adjust mathematical models to experimental data. The fruits were purchased at the Campina Grande - PB, selected according to the degree of maturity appropriate for processing and absence of physical damage (injuries), washed and sanitized with sodium hypochlorite solution, then they were manually pulped to separate the solid fractions, pulp, peel and seeds. The drying was carried out in a forced air circulation oven, at temperatures range 45, 50 and 55 °C. The experimental drying data were adjusted to the Page, Midili and Henderson and Pabis models. The kinetics of the Jabuticaba shells showed that the temperature influenced the drying process, and it was found that the drying constant “k” increased with its elevation. In addition, the Midili model showed a better fit compared to the other methods.